From Language Learning Media to Representing Turkish Culture: Cultural Content in Turkish Language Textbooks - Mualimin, Mualimin; Fathiyakan, Fathiyakan; Rahayu, Siti (Educative: Jurnal Ilmiah Pendidikan, 2023)
Language has a close relationship with culture, so that language learning often uses cultural content as a learning medium. Therefore this study aims to analyze the cultural content in textbooks for learning Turkish and its relation as a medium of learning between Turkish languages. This study is qualitative research with a literature study approach. The source of the data in this study was the textbook for learning Turkish, namely "Istanbul Yabancılar İçin Türkçe Ders Kitabı". Data were collected by observing the content in the book. The data obtained were then analyzed using the Miles and Huberman qualitative analysis model: data reduction, data display, and conclusion. The findings in this study lead to the conclusion that cultural content is a crucial and inseparable part of the substance of the book "Istanbul Yabancılar İçin Türkçe Ders Kitabı" as a Turkish language textbook. At this level, the cultural content has two functions at once: bridging understanding related to Turkish grammar and representing the cultural identity of the Turkish people to international students.